LAS 5S COMO HERRAMIENTA DE PREVENCIÓN DE ACCIDENTES E INCIDENTES DE TRABAJO EN LA EMPRESA EXPORTADORA DE CACAO AGROLAYA S.A - Montoya Monserrate, Jelitza Narcis (2023)
The 5S methodology, recognized for its effectiveness in continuous improvement, was applied in the company Agrolaya S.A. through an analysis of your current situation. The objective was to identify deficiencies in the work areas and develop an action plan to improve the processes related to order, cleanliness and continuous improvement.